2017
DOI: 10.1371/journal.pone.0168835
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Patient Education Improves Glycaemic Control in Diabetes Compared to Conventional Education: A Randomised Controlled Trial in a Nigerian Tertiary Care Hospital

Abstract: BackgroundDiabetes is now a global epidemic, but most cases are now in low- and middle-income countries. Diabetes self-management education (DSME) is key to enabling patients to manage their chronic condition and can reduce the occurrence of costly and devastating complications. However, there is limited evidence on the effectiveness of different DSME programmes in resource limited settings.MethodsWe conducted an unblinded, parallel-group, individually-randomised controlled trial at the University of Calabar T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
90
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(95 citation statements)
references
References 20 publications
4
90
1
Order By: Relevance
“…weight, blood pressure, lipids, glycaemic control) and reduction in the risk of CV events. [85][86][87][88] Studies assessing the impact of DSME programmes vary in a number of parameters such as methods (e.g. patient empowerment, 38 intensive interventions, 62,77 digital health technology, 40 providers of DSME, duration, intensity and content of education, follow-up intervals and participant characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…weight, blood pressure, lipids, glycaemic control) and reduction in the risk of CV events. [85][86][87][88] Studies assessing the impact of DSME programmes vary in a number of parameters such as methods (e.g. patient empowerment, 38 intensive interventions, 62,77 digital health technology, 40 providers of DSME, duration, intensity and content of education, follow-up intervals and participant characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term glycemic control is one of the strongest clinical-outcome indicators of efficient diabetes management and health outcomes ( 7 ). The very limited research in Africa has provided inconsistent evidence regarding the clinical significance of DSME ( 7 , 20 , 21 , 29 , 47 49 ). The current study showed a significant mean HbA1c drop within both intervention and comparison groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, the very limited research in Africa has resulted in conflicting evidence regarding the effectiveness of DSME on long-term glycemic control and other clinical outcomes. An intensive and structured DSME education given by nurses and physicians for 6 months showed significant reduction in HbA1c among those who received an intervention ( 20 ). However, group-based DSME led by ley health promoters in underserved urban South Africa did not show significant mean difference in HbA1c between groups.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies already showed that current information provision to SSc patients is insufficient in The Netherlands [19,20]. Accessible education improves clinical parameters and therapeutic adherence [21][22][23]. Importantly, it also increases empowerment and strengthens patients' position in decision-making processes [24][25][26].…”
Section: Discussionmentioning
confidence: 99%